Deteksi Tepi untuk Mendeteksi Kondisi Otak Menggunakan Metode Prewitt - Irzal Arief Wisky; Sumijan (Jurnal Teknologi, 2022)
The brain is an organ that is in the head as a controller of all functions of the human body, thus enabling humans to think and solve problems. Brain health conditions are very important in keeping the body's functions running properly. Several diseases can adversely affect brain health, such as cancer, tumors, meningitis, encephalitis and other brain diseases. Brain conditions can be identified through Magnetic resonance imaging (MRI). This study aims to identify brain conditions based on Brain Edge Detection on MRI images. The technique used is Prewitt method. The stages of the process carried out in edge detection begun with the pre-processing process in reducing the noise contained in the MRI image. The number of MRI images tested was 25. The results of this study can localize the edges of the image very well. The accuracy of this study is 85%, so this research can be recommended in identifying brain organs.